1918
DOI: 10.5962/bhl.title.40923
|View full text |Cite
|
Sign up to set email alerts
|

I. Notes on insects bred from the bark and wood of the American larch

Abstract: Entered at the Postofflce at Syracuse as second-class mall matter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1967
1967
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Sex counts show a primary sex ratio of 1/2 (27,30); I know of only one possible exception (31). In response to the male's attractant scent, several females (but not more than eight) colonize the nuptial chamber of a successful male, are mated by him, and construct radiating egg galleries.…”
Section: Sex Ratios With Polygynymentioning
confidence: 99%
“…Sex counts show a primary sex ratio of 1/2 (27,30); I know of only one possible exception (31). In response to the male's attractant scent, several females (but not more than eight) colonize the nuptial chamber of a successful male, are mated by him, and construct radiating egg galleries.…”
Section: Sex Ratios With Polygynymentioning
confidence: 99%
“…3a and c). Although sucrose gradient ultracentrifugation is the method of choice for separation of organelles [19], some non-microneme contamination does occur and the microneme fraction in this case was also found to contain a trace of rhoptry protein (Fig. 3b).…”
Section: Screening Pmf Datamentioning
confidence: 92%
“…This finding was confirmed in a larger series of tumors observed by the same group where 61% of the functioning malignant pancreatic endocrine tumors were found to secrete a-hCG in men and 38% of the tumors in women. 29 In addition, a-hCG secretion was reported to occur in three of ten patients with malignant gastrinomas but in none of 16 patients suffering from benign gastrinomas. 30 The highest incidence (85%) of elevated serum levels of hCG in the presence of a malignant pancreatic endocrine tumor was found in the 16 patients observed by Oberg and Wide.3' These authors found P-hCG to be predominantly secreted (69% of malignant pancreatic endocrine tumors).…”
Section: Fig 2 A-hcg-immunoreactivity In the Cytoplasm Of Several Tmentioning
confidence: 99%